Cyber Forensics, 2nd Edition - Marcella, Albert; Menendez, Doug; Safari, an O'Reilly Media Company (Auerbach Publications, 2010)
Designed as an introduction and overview to the field, Cyber Forensics: A Field Manual for Collecting, Examining, and Preserving Evidence of Computer Crimes, Second Edition integrates theory and practice to present the policies, procedures, methodologies, and legal ramifications and implications of a cyber forensic investigation. The authors guide you step-by-step through the basics of investigation and introduce the tools and procedures required to legally seize and forensically evaluate a suspect machine. Updating and expanding information on concealment techniques, new technologies.
Made available through: Safari, an O'Reilly Media Company.
Online resource; Title from title page (viewed December 19, 2010)
Keywords: Computer crimes -- Investigation -- Handbooks, manuals, etc; Computer crimes -- Investigation; Criminalité informatique -- Enquêtes -- Guides, manuels, etc; Criminalité informatique -- Enquêtes.; Computer crimes -- Investigation; handbooks; Handbooks and manuals; Handbooks and manuals; Guides et manuels